Colon Cancer Screening in Concierge Practice. Issue 6 (June 2017) - Nguyen, Elizabeth; Mehta, Shivani; Yates, Scott W.; Schrader, M. Keith; Martin, Michael C.
Abstract : Objectives: This study evaluated the effectiveness of the Center for Executive Medicine (CEM) concierge primary care practice on preventive colorectal cancer (CRC) screening rates relative to local and national comparator data. Methods: We performed an electronic medical record search encompassing our entire patient population who are between the ages of 50 and 75 years to determine the rate of CRC screening. We compared this rate with the average rate of Medicare Advantage plans reported by our Independent Physician Association (IPA) in 2015 and national health plans reported by the National Committee for Quality Assurance in 2014. Results: The CEM had a CRC screening rate of 90.2%, which was significantly higher than local IPA Medicare Advantage plans (63.3%) and National Committee for Quality Assurance national plans (57.7%–66.5%). CEM members were significantly more likely than were IPA members to undergo screening (odds ratio 1.425, 95% confidence interval 1.348–1.507, P < 0.0001). Conclusions: These results suggest that the CEM practice strategy and processes increase CRC screening rates. Abstract : The authors performed an electronic medical record search of their concierge medicine membership practice patient population (ages 50–75 years) to determine the rate of screening for colorectal cancer (CRC). The CRC screening rate of 90.2% was significantly higher than that of local Independent Physician Association Medicare Advantage plans (63.3%) and National Committee for Quality Assurance national plans (57.7%–66.5%). Member patients were significantly more likely to undergo screening than local Independent Physician Association members, with an odds ratio of 1.425 (95% confidence interval 1.1582–1.7532, P = 0.0008). Factors that the authors believe may affect rates of CRC screening are examined.